'Achieved not given': human rights, critique and the need for strong foundations. Issue 3 (24th March 2017) - Li, Yingru; McKernan, John
ABSTRACT: In this article we focus critically on the normative foundations of the project outlined by Benjamin Gregg in The Human Rights State (2016). In developing our analysis of Gregg's project, we consider it in the context of the inspiration it draws from the work of Hannah Arendt and Jacques Rancière. We argue that Arendt does not give Gregg any robust support for his anti-foundationalism, and that Rancière's politics of dissensus makes an uneasy ally for Gregg's constructivism. We argue that we need strong moral foundations to motivate critique and ground valid construction, and that they need not draw us back into the authoritarianism so often associated with classical foundations on which human rights claims have sometimes relied. We suggest that the right kind of thin but strong moral foundations are most clearly articulated in the work of the critical theorist Rainer Forst, and that Forst's constructivism and his emphasis on dissensus makes his perspective particularly compatible with Gregg's project. In the final parts of the article, we expose what we see as the unacknowledged normative foundations of Gregg's position. We conclude by briefly examining the practical significance of his neglect of those foundations and the moral context that are crucial for tackling the governance gap in business human rights issues.